Analyzing a behavioral-risk-chain network of accidents in the Chinese building construction. Issue 6 (March 2019) - Guo, Shengyu; Zhou, Xinyu; Gong, Peisong; Tang, Bing
Abstract: To deeply understand the impact of unsafe behavior on accidents, this paper analyzes a behavioral-risk-chain-network of accidents (BRCNA) in the Chinese building construction based on complex networks theory. Firstly, unsafe behaviors are classified from safety standards and operating procedures. Secondly, rules to form behavioral risk chains are defined, and then BRCNA is established from accident cases in the Chinese building construction. Besides, Pajek is used to construct the network model. Finally, the average path length, diameter and clustering coefficient are calculated and analyzed in BRCNA. The results show BRCNA has short average path length and high clustering coefficient, which indicates it has the characteristics of a small-word network with high transmission efficiency. The interactions among unsafe behaviors on building construction accidents are identified. It is of theoretical and practical significance on safety management and accident prevention in the Chinese construction industry.